Cultural and Social Identity in Clothing Matters “Different Cultures, Different Meanings” (European Journal of Behavioral Sciences, 2018)
This article is concerned with the matters of clothing as a cultural and social identity which is understood to be a part of a symbol that can explain a person’s identity. This has been felt by humans since ancient times and developed along with the development of human culture and civilization. From this point of view, we can learn things related to clothing. Every country or region has different characteristics as an identity that is manifested in the form of traditional or distinctive clothing, customs, folk songs, and language. This can be used as a characteristic of every country or region that generally aims to be easily recognized by the wider community. One of the identities of a region in the form of clothing or clothing used. The need to know the characteristics of other regional or country cultures is very important in adding insight as well as citizens can recognize the culture or identity of other regions or countries so as not to be blind in insight and not favor selfishness to recognize the identity of other regions or countries. So many regions and countries have different characteristics. Possibly there are similarities that originate from where they came from like if a country once united and then divorced to establish its own country, this can create equality.